Forming “leadership” competency in institutes of higher education - Dar'ya P. Shchetinina; Svetlana S. Zinchenko (Rossijskij psihologičeskij žurnal., 2018)
The article deals with the problems of forming leadership competencies in institutes of higher education. Requirements of consumers of educational services – the state, universities, students, and employers – have confirmed the relevance of this issue. Being based on the analysis of the Federal State Educational Standard  of areas of economics (economics, management, personnel management, and etc.) the paper presents an original questionnaire for employers, teachers, and students. The questionnaire highlighted the main common cultural and professional competencies and revealed the most needed knowledge, skills, and abilities of young professionals. The paper provides an overview of domestic and foreign research of leadership in the student’s environment, as well as the results of the carried out study. The analysis of theoretical approaches to leadership enabled to generalize and concretize the concept of “leadership competence”. Thus, the article defined leadership competence as a leadership metacompetence which made it possible to cultivate leadership qualities, adapt to new conditions, and also facilitated the acquisition of other competencies. The study, which involved students, teachers, and employers of the Southern Federal District, distinguished the main components of “leadership” competence, highlighted the main leadership qualities in students, and assessed the leadership qualities in heads of student groups. Research methods included a number of author’s questionnaires. Thus, the questionnaire consisting of 45 items (in the framework of the technique of “360 degrees”) was used for assessing the leadership qualities in the heads of student groups. A comprehensive approach of testing, enabling to cover the problem from different points of view and levels of hierarchy (students, teachers, curators, and heads) was the main purpose of this assessing. The results of the carried out study made it possible to specify the definition of “leadership” competence, highlight the main characteristics of leadership qualities in the student’s environment, and suggest directions of forming leadership skills in institutes of higher education.